Application of IoT with haptics interface in the smart manufacturing industry - Contreras Masse, Roberto (2019)
The emerging technologies that make up Industry 4.0, include the Internet of Things and big data. The haptic interfaces have been used in different industries, but apparently, they are not integrated with the two technologies mentioned above. This work aims to know what the current use of IoT is, haptic interfaces and big data in the manufacturing industry. In turn, the fact of implementing an IoT platform leads to selecting an architecture that adapts to the needs of a specific organization. That is why this work also seeks to describe the IoT architectures available in the literature. Finally, we seek to know what the potential benefits for the manufacturing industry are combining IoT, haptic interfaces and big data in an intelligent environment enabled by machine learning. To have a better understanding, this work includes the description of the relevant concepts of the topic, including the description of supervised learning algorithms. In the end, this work allows us to open the door to other areas of research for future research.